2007
DOI: 10.2111/1551-5028(2007)60[471:eopfof]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphate Fertilization on Flooding Pampa Grasslands (Argentina)

Abstract: We postulate that phosphorus (P) fertilization may increase above-ground net primary productivity (ANPP) of rotationally grazed rangelands without reducing the legume component, as does N fertilization. In doing so, we evaluated the effect of phosphate fertilization on the production and relative contribution of legumes and grasses of native and old tall fescue (Festuca arundinacea Schreb) grasslands; we recorded annual production, seasonal productivity, and biomass contribution of each component. The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…This bottom-up control of herbivore populations should be evidenced by the enhancement of both plant productivity and insect abundance with high soil P availability. Although P has been proposed as one of the most important limiting factors for productivity of the Flooding Pampa grasslands due their chronic P shortage in soils, the evidence is not conclusive (Collantes, Stofella, Ginzo, & Kade, 1988;Ginzo, Collantes, & Caso, 1982;Rodríguez, Jacobo, Scardaoni, & Deregibus, 2007;Semmartin, Oyarzabal, Loretti, & Oesterheld, 2007). In particular, studies evaluating the addition of P in a natural grassland with very low cover of N-fixing legumes (Semmartin et al, 2007) and in an old pasture with tall fescue as main component (Rodríguez et al, 2007) found no significant response in terms of above-ground biomass production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bottom-up control of herbivore populations should be evidenced by the enhancement of both plant productivity and insect abundance with high soil P availability. Although P has been proposed as one of the most important limiting factors for productivity of the Flooding Pampa grasslands due their chronic P shortage in soils, the evidence is not conclusive (Collantes, Stofella, Ginzo, & Kade, 1988;Ginzo, Collantes, & Caso, 1982;Rodríguez, Jacobo, Scardaoni, & Deregibus, 2007;Semmartin, Oyarzabal, Loretti, & Oesterheld, 2007). In particular, studies evaluating the addition of P in a natural grassland with very low cover of N-fixing legumes (Semmartin et al, 2007) and in an old pasture with tall fescue as main component (Rodríguez et al, 2007) found no significant response in terms of above-ground biomass production.…”
Section: Discussionmentioning
confidence: 99%
“…Although P has been proposed as one of the most important limiting factors for productivity of the Flooding Pampa grasslands due their chronic P shortage in soils, the evidence is not conclusive (Collantes, Stofella, Ginzo, & Kade, 1988;Ginzo, Collantes, & Caso, 1982;Rodríguez, Jacobo, Scardaoni, & Deregibus, 2007;Semmartin, Oyarzabal, Loretti, & Oesterheld, 2007). In particular, studies evaluating the addition of P in a natural grassland with very low cover of N-fixing legumes (Semmartin et al, 2007) and in an old pasture with tall fescue as main component (Rodríguez et al, 2007) found no significant response in terms of above-ground biomass production. Light availability is an important restriction for primary production in humid and subhumid grasslands such as the Flooding Pampa grasslands (Borer et al, 2014;Milchunas, Sala, & Lauenroth, 1988;Semmartin & Oesterheld, 2001;Semmartin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the Salado River Basin, Argentina, the proportion of cropland has increased in areas historically used for raising cattle [25]. the Flooding Pampa [5,26]. Some of these strategies involve identifying and selecting was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 99%
“…), or rotational grazing with phosphate fertilization, which increases the production of C 3 annual grasses and legumes (Rodríguez et al. ). Both alternatives reduce the seasonal variability of plant production by increasing winter forage production and lead to an improvement in rangeland condition and carrying capacity (from 0.6 to 1.0 Animal Units ha −1 ).…”
Section: Discussionmentioning
confidence: 99%